The firebird - Kelman, Marcy; Borkin, Jeff.; Song, Aram (New York : Disney Press, 2007)
The Little Einsteins use teamwork to rescue the magical, musical Firebird of Russia from the evil ogre Katschai.
"Based on the episode written by Jeff Borkin.".
"Disney's little Einsteins.".
2.6
K-3
Keywords: Animals, Mythical -- Juvenile fiction; Magic -- Juvenile fiction; Animals, Mythical -- Fiction; Magic -- Fiction; Friendship -- Fiction; Music -- Fiction; Mythical animals -- Fiction; Russia -- Fiction